ANALISIS TANAMAN PUTRI MALU ( MIMOSA PUDICA ) YANG DI LAKUKAN DILAPANGAN SEPAK BOLA STKIP AL MAKSUM LANGKAT - Kamariah Kamariah; Riski Ananda; Riana Safitri (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to observe and analyze the seismonastic movement responses of the Mimosa pudica (Mimosa pudica) in a pair of leaflets and a leaf stalk, as well as their relationship to morphological structures such as the base of the leaf stem, leaf branches, and the stem as a whole. The movement response was assessed by observing the time it takes for the leaf to close after being stimulated and the time it takes to reopen. The method used was direct observation with documentation in the form of photographs of each plant part: a pair of leaflets, leaf branches, the main stem, and the base of the leaf stem. The study was conducted under natural light conditions without additional artificial stimuli other than light touch. The results showed that leaf closure occurred rapidly, averaging between 1–3 seconds after the touch stimulus, while the reopening time varied between 10–25 minutes depending on the leaf part stimulated. The pair of leaflets showed the fastest response in closing, while the main stem did not exhibit seismonastic movements but acted as a relay for the movement impulse. Visual documentation supported the observations by demonstrating differences in sensitivity levels between plant parts. This study strengthens the understanding of plant defense mechanisms against external stimuli and the important role of leaf structure in response to stimuli.